Health Systems Analysis for Better Health System Strengthening - Berman, Peter; Bitran, Ricardo (2013)
Health system strengthening and reform are often necessary actions to achieve better outcomes. The World Bank's 2007 strategy for health, nutrition, and population emphasizes the importance of health system strengthening for results. This paper proposes 'health systems analysis' as a distinct methodology that should be developed and practiced in the design of policies and programs for health system strengthening. It identifies key elements of health systems analysis and situates them in a logical framework supported by a wide range of data and methods and a sizable global literature. Health systems analysis includes evidence on health system inputs, processes, and outputs and the analysis of how these combine to produce the outcomes. It considers politics, history, and institutional arrangements. Health systems analysis proposes causes of poor health system performance and suggests how reform policies and strengthening strategies can improve performance. It contributes to implementation and evaluation. Examples from Mexico, Ethiopia, and Turkey illustrate the positive contributions health systems analysis has made to development of successful health system strengthening policies. Health systems analysis should be an integral part of good practice in health system strengthening efforts, including planning, policy development, monitoring, and evaluation. Health systems analysis can be conceived in a coherent and logical fashion and can be practiced and improved.